Exercise, Health Outcomes, and Pædiatric Obesity: A Systematic Review of Meta-Analyses - Garcia-Hermoso, A (Elsevier Ltd, 2019)
Objectives: This study is a systematic review of meta-analyses that have addressed the effects of exercise-based interventions alone and the health outcomes (anthropometric, body composition, cardiometabolic, hepatic, vascular, and cardiorespiratory fitness parameters) in overweight and obese children and adolescents. Design: Systematic review of meta-analysis. Methods: Six electronic sources were searched. The inclusion criteria were: children and/or adolescents classified as overweight or obese, and previous systematic reviews and meta-analyses that included exercise interventions compared to a control group. Standardized mean differences, risk of bias, heterogeneity, and small-study effects were calculated. Subgroup analyses (intervention characteristics) were done. Results: Eighteen meta-analyses met the inclusion criteria. The results showed improvements in some anthropometric and body composition (body mass, BMI, BMI z-score, central obesity, fat mass) and cardiometabolic (TG, fasting glucose, fasting insulin) parameters, and in cardiorespiratory fitness. For the cardiometabolic and vascular parameters, aerobic programs and interventions showed themselves to be effective if they were of four to 12 weeks, or involved a total exercise time of at least 1500 min, or involved sessions of at least 60 min. Conclusions: The study provides indications of the appropriate dose of exercise with which to reduce health problems in the obese young population. © 2018 Sports Medicine Australia